The impact of Chinese auditors’ values on their ethical decision-making in China - Fan, Ying Han (Curtin University, 2008)
This study involves a first attempt to identify Chinese auditors’ values and examines their effects on ethical ideologies and ethical judgments and intentions. A survey methodology is used and the survey instrument includes a self-administered questionnaire and a short auditing ethical case. A sample of Chinese CPAs with auditing experience was drawn from accounting firms located in Shenzhen, Hangzhou, Beijing, and Kunming cities during 2006-7. Three hundred and twenty-five useable responses were received. The theoretical framework for this study is based on Forsyth’s (1980) model of ethical ideologies. This study identifies Chinese auditors’ cultural values as (1) Chinese traditional cultural values, (2) interpersonal relationships (guanxi), and (3) attitudes towards money. This study posits that Chinese auditors’ cultural values will impact on their ethical ideologies and that their ethical judgments and intentions are, in turn influenced by the ideologies they prefer. In this study, Chinese auditors’ ethical judgments and intentions are examined using a well understood ethical dilemma in auditing, specifically whether an auditor should accept a client’s suggestion to inappropriately alter the financial position or to adhere to accounting and professional standards. Four research questions are proposed in this study: 1. What national cultural values best describe Chinese auditors? 2. How do Chinese cultural values impact ethical ideologies (i.e., Idealism and Relativism) as they apply to practicing auditors? 3. Do identifiable ethical ideologies, adopted by auditors, influence the decision making process in issues relating to audit independence? In particular, ethical judgments and intentions. 4. How do certain contextual matters, namely firms’ ethical culture and personal factors influence ethical ideologies?Chinese auditors’ beliefs about their national cultural values are measured using the Chinese Cultural Values (CVS) used in the Chinese Culture Connection (1987). Chinese auditors’ guanxi orientations are measured using a 12 item scale based on Ang and Leong’s (2000) 9 items favour-seeking guanxi scale and three items constructed by the author concerned with rent-seeking guanxi orientations. Chinese auditors’ attitudes towards money are measured using Tang and Chiu’s (2003) the Love of Money Scale (LMOS) scale. Chinese auditors’ beliefs about their firms’ ethical cultures are measured using Hunt et al.’s (1989) corporate ethical values scale. Chinese auditors’ ethical ideologies are determined by using Forsyth’s (1980) ethical position questionnaire (EPQ). Finally, Chinese auditors’ ethical judgments and intentions are measured using an auditing case study. The major statistical methods used in this study are descriptive, t-tests, correlations, and regression analysis. The following significant results are presented in this study: 1. Chinese auditors display strong views about their traditional cultural values in four of the five national dimensions, the exception being Confucian Work dynamism past orientation. Young auditors appear less concerned with Integration issues compared to their older counterparts. Again, younger and less experienced auditors display less interest in the Human-heartedness dimension compared to their older counterparts. Auditors with Masters Degrees identify less with Confucian Work dynamism future orientations when compared to those who hold a Bachelors degree.Attitudes towards the Confucian Work dynamism dimension future orientation are found to be positively associated with Idealism, however attitudes relating to Confucian Work dynamism dimension past orientation component are found to be negatively associated with Idealism. Further, attitudes relating to Confucian Work dynamism dimension past orientation component are found to be negatively associated with Relativism. 2. Chinese auditors display significantly higher mean scores in both favour-seeking and rent-seeking guanxi orientations. Young and less experienced auditors are more likely to use rent-seeking guanxi than older and experienced auditors. Chinese auditors’ rent-seeking guanxi orientations are found to be negatively associated with Idealism and both favour-seeking and rent-seeking guanxi orientations are found to be positively associated with Relativism. 3. Chinese auditors’ attitudes towards money are high in two of the four dimensions relating to the love of money, namely the importance of money and the desire to be rich dimensions. Their attitudes towards money are significantly higher than for Hong Kong employees. Male auditors displayed significantly higher mean scores in the desire to be rich dimension than female auditors. Young auditors have significantly higher mean scores in the success and motivator dimensions compared to older auditors. Chinese auditors’ beliefs about the importance of money are found to be positively associated with Relativism. Interestingly, no association with Idealism was identified in this study. 4. Chinese auditors have stronger beliefs about their firms’ ethical cultures to compare the mid-point value but their beliefs are significantly lower than for American subjects.Junior and senior auditors are less likely to believe their managers display unethical behavior compared to accounting firm partners. Auditors employed in work environments where punishment systems exist are likely to disclose attitudes that are positively associated with Idealism. Alternatively, auditors employed in work environments where managers are believed to display unethical behaviour are likely to disclose attitudes that are positively associated with Relativism. 5. Chinese auditors display relatively higher ethical positions (on both Idealism and Relativism) to compare the mid-point value. Males hold stronger relativist positions than females and older auditors are more idealistic than their youthful counterparts. Auditors who hold senior positions are more likely to be relativists compared to juniors. Chinese auditors’ ethical judgments are found to be positively associated with Idealism and negatively associated with Relativism. However, their ethical intentions are only found to be negatively associated with Relativism. Young auditors appear less ethical in terms of their judgments than older auditors and less experienced auditors are less intentioned compared to experienced auditors. This study contributes to our understanding of Chinese auditors’ values and their ethical ideologies and the effects these have on their ethical judgments and intentions. It is the first research to include a wide range of ethical decision-making factors within a business context in China using qualified CPAs. It is believed that valuable insights have been gained about the various cultural factors influencing ideological processes and how these flow through to the decision making level.The study also contributes to the existing body of knowledge by providing additional evidence that ethical decision making is a universal concept involving moral philosophies such as those suggested by Forsyth (1980) and Hunt and Vitell (1986) and applies in an auditing context in China. Moreover, this study develops a rent-seeking guanxi scale based on Su et al.’s (2003) classification of guanxi orientations and Ang and Leong’s (2000) guanxi scale. It contributes by providing a scale to measure the extent to which business relationships involves back door deals and power dependence. One of the significant contributions of this study is that it contributes to the construction of a meaningful measure for the guanxi scale which includes favour-seeking guanxi and specifically for the first time, rent-seeking guanxi. Thus a confirmatory analysis with an independent sample could be used in the future to re-test the guanxi scale with the two dimensions developed in this study. contributions of this study is that it contributes to the construction of a meaningful measure for the guanxi scale which includes favour-seeking guanxi and specifically for the first time, rent-seeking guanxi. Thus a confirmatory analysis with an independent sample could be used in the future to re-test the guanxi scale with the two dimensions developed in this study.